Repair of Cerebrospinal Fluid Fistula from an Invasive Skull Base Prolactinoma Using a Septal Mucosal Vascularized Flap: Technical Case Report - Little, Andrew S. (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2013)
Repair of spontaneous cerebrospinal fluid (CSF) fistulas in patients with invasive skull base prolactinomas represents a surgical challenge because of the many sites of potential leak around the tumor and the possibility of developing additional sites of leak as the tumor regresses on dopamine agonist therapy. Little has been published on effective methods for treating this problem. In this case, a vascularized nasoseptal flap was used to repair a spontaneous CSF leak in a 31-year-old male with an invasive prolactinoma who was commenced on dopamine agonist therapy. The patient underwent successful multilayer repair of the fistula with a nasoseptal vascularized flap and abdominal rectus fascia. After 3 months of follow-up, he has had no CSF leak. CSF fistulas caused by skull base prolactinomas can be repaired successfully using a vascularized nasoseptal flap. Long-term follow-up will determine the durability of this repair technique.
Keywords: septal mucosal flap; prolactinoma; cerebrospinal fluid leak